Factor Analysis of Student Learning Difficulties Using Powerpoint Media - Putra, Chandra Anugrah; Sumardy, M. (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This learning media is useful for teachers because using media as a tool can help teachers explain the material being conveyed to students. Public Vocational Secondary School-2 Kasongan has sufficient facilities such as LCDs, laptops, and computers, but teachers do not utilize the existing facilities. Therefore, teachers must be able to create interesting learning using PowerPoint media so that students are interested in following the learning provided by the teacher. This research aims to determine the factors influencing students’ difficulties using Microsoft PowerPoint. This research was conducted at Public Vocational Secondary School -2 Kasongan. The research object was the class data analysis process, checking data validity. The results of this research show that the factors that influence the difficulty in using Microsoft PowerPoint at Public Vocational Secondary School-2 Kasongan are: 1) several students are technologically clueless and have knowledge of the basics of PowerPoint. 2) Students do not understand the function of using PowerPoint features. 3) Lack of creative ideas and creativity in creating attractive PowerPoint designs.